Description of a model to facilitate male involvement in the reproductive health context by the registered nurses - Justus, Amukugo Hans; Jooste, Kareen; Nangombe, Julia Paula (International Journal of Advanced Nursing Studies, 2015)
The aim of this article is to describe a model to facilitate male partner involvement in the RH context. The findings in chapter 3, step1 – concept analysis – which comprised the identification, definition and classification of concepts and the construction of an interrelationship between concepts and statements (chapter 4), formed the basis for the development of this model. This model to facilitate male partner involvement in RH is based on the theory generation of Chinn and Kramer (1991). The central concepts are defined by using the rules described by Rossouw (2000/1,) and Copi and Cohen (1996). Lastly, the model evaluation has been done in accordance with the method of Chinn and Kramer (1991).
Keywords: Description; Model; Male Involvement; Reproductive Health; Registered Nurses.